Environmental and anthropogenic drivers of watercress (Nasturtium officinale) communities in char-lands and water channels across the Swat River Basin: implication for conservation planning - Khan, Nasrullah; Ullah, Rafi; Okla, Mohammad K.; Abdel-Maksoud, Mostafa A.; Saleh, Ibrahim A.; Abu-Harirah, Hashem A.; AlRamadneh, Tareq Nayef; AbdElgawad, Hamada (Frontiers in Plant Science, 2023)
Recent anthropogenic sources and excess usage have immensely threatened the communities and habitat ecology of this region’s medicinally and economically significant crops. Therefore, our study aims to evaluate the community structure and related environmental characteristics sustaining Nasturtium officinale communities along the river basin (RB) in Northwest Pakistan, using the clustering procedure (Ward’s method) and Redundancy analysis (RDA). From 340 phytosociological plots (34 × 10 = 340), we identified four ecologically distinct assemblages of N. officinale governed by different environmental and anthropogenic factors for the first time. The floristic structure shows the dominance of herbaceous (100%), native (77%), and annual (58.09%) species indicating relatively stable communities; however, the existence of the invasive plants (14%) is perturbing and may cause instability in the future, resulting in the replacement of herbaceous plant species. Likewise, we noticed apparent variations in the environmental factors, i.e., clay percentage (p = 3.1 × 10−5), silt and sand percentage (p< 0.05), organic matter (p< 0.001), phosphorus and potassium (p< 0.05), and heavy metals, i.e., Pb, Zn, and Cd (p< 0.05), indicating their dynamic role in maintaining the structure and composition of these ecologically distinct communities. RDA has also demonstrated the fundamental role of these factors in species–environment correlations and explained the geospatial variability and plants’ ecological amplitudes in the Swat River wetland ecosystem. We concluded from this study that N. officinale communities are relatively stable due to their rapid colonization; however, most recent high anthropogenic interventions especially overharvesting and sand mining activities, apart from natural enemies, water deficit, mega-droughts, and recent flood intensification due to climate change scenario, are robust future threats to these communities. Our research highlights the dire need for the sustainable uses and conservation of these critical communities for aesthetics, as food for aquatic macrobiota and humans, enhancing water quality, breeding habitat, fodder crop, and its most promising medicinal properties in the region.